2016
DOI: 10.1155/2016/6073051
|View full text |Cite
|
Sign up to set email alerts
|

The Difference of Structural State and Deformation Behavior between Teenage and Mature Human Dentin

Abstract: Objective. The cause of considerable elasticity and plasticity of human dentin is discussed in the relationship with its microstructure. Methods. Structural state of teenage and mature human dentin is examined by using XRD and TEM techniques, and their deformation behavior under compression is studied as well. Result. XRD study has shown that crystallographic type of calcium hydroxyapatite in human dentin (calcium hydrogen phosphate hydroxide Ca9HPO4(PO4)5OH; Space Group P63/m (176); a = 9,441 A; c = 6,881 A; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…Panfilov et al showed higher tensile strength of mature rather than teenage dentin (549.5 ± 26.9 MPa vs 445.2 ± 30.9 MPa, respectively). 28 Within the limitations of this study we can suggest the transversely isotropic behavior of dentin and the anisotropy ranged from 6.9 to 35.2%, depending on the dentin location. The numerical and analytical dentin homogenization presented similar results.…”
Section: Discussionmentioning
confidence: 60%
“…Panfilov et al showed higher tensile strength of mature rather than teenage dentin (549.5 ± 26.9 MPa vs 445.2 ± 30.9 MPa, respectively). 28 Within the limitations of this study we can suggest the transversely isotropic behavior of dentin and the anisotropy ranged from 6.9 to 35.2%, depending on the dentin location. The numerical and analytical dentin homogenization presented similar results.…”
Section: Discussionmentioning
confidence: 60%
“…, Panfilov et al . ) and the effect of long‐term occlusal force during mastication that acted as a risk factor for root fracture (Chan et al . , Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, based on a comparison of the clinical characteristics between HRF and VRF in posterior teeth, VRF in endodontically treated teeth were encountered most commonly in patients between 40 and 60 years old (Testori et al 1993, Chan et al 1999, Tsai et al 2001, whereas VRF in nonendodontically treated teeth and HRF (the majorities of teeth were nonendodontically treated) had an older age distribution (Yang et al 1995, Chan et al 1999, Wang et al 2011. Previous studies have suggested that increasing age may result in structural changes within the tooth such as alteration in dentine elasticity (Xu et al 2014, Panfilov et al 2016) and the effect of longterm occlusal force during mastication that acted as a risk factor for root fracture (Chan et al 1999, Lin et al 2008. Whether the age-related structural change or long-term usage of teeth resulted in HRF in posterior teeth is unclear and needs to be investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we attempted to eliminate some of the variables which are inevitably present in in vitro studies evaluating the mechanical behavior of pulpless teeth. Human teeth, even within a certain range of acceptability, present inherent variations in size and morphology and may behave differently under mechanical loads due to chemical-physical differences, amorphous phase content and elastic modulus 11 . The use of identical resin replicas constructed from only one dental element with the same external and intracanal morphology were used to standardize the roots dimensions and ensure specimens uniformity.…”
Section: Discussionmentioning
confidence: 99%